Ultrahard magnetism from mixed-valence dilanthanide complexes with metal-metal bonding - Gould, Colin A; McClain, K Randall; Reta, Daniel; Kragskow, Jon G C; Marchiori, David A; Lachman, Ella; Choi, Eun-Sang; Analytis, James G; Britt, R David; Chilton, Nicholas F; Harvey, Benjamin G; Long, Jeffrey R (Science (American Association for the Advancement of Science), 2022)
Magnetic effects of lanthanide bonding Lanthanide coordination compounds have attracted attention for their persistent magnetic properties near liquid nitrogen temperature, well above alternative molecular magnets. Gould . report that introducing metal-metal bonding can enhance coercivity. Reduction of iodide-bridged terbium or dysprosium dimers resulted in a single electron bond between the metals, which enforced alignment of the other valence electrons. The resultant coercive fields exceeded 14 tesla below 50 and 60 kelvin for the terbium and dysprosium compounds, respectively. —JSY